Cyanobacterial persistence and influence on microbial community dynamics over 15 years in induced biocrusts. (23rd November 2021) - Lan, Shubin; Wu, Li; Adessi, Alessandra; Hu, Chunxiang
Summary: Biocrusts provide numerous ecological functions in drylands. Recovering biocrusts via cyanobacterial inoculation recently gathered interest for ecological restoration, yet it still lacks long‐term experiments to unravel biocrust community dynamics. To examine how cyanobacterial inoculants influenced local microbial community and biocrust development, we observed a 2 km 2 (Qubqi Desert, China) inoculation experiment after 10 and 15 years, following biocrust formation. Our results revealed that biocrust development was in line with ecological regime shift, providing evidence for biocrust community succession, from cyanobacteria‐ to moss‐dominated types. Associated with biocrust development, microbial communities differed significantly with less specialists compared to shifting sands. Cyanobacterial community analysis showed that Microcoleus vaginatus and Scytonema javanicum are an ideal inoculating model, as they were still dominating the community after 15 years since inoculation, while other nitrogen‐fixing cyanobacteria occurred profusely with biocrust development. Biocrust community composition combined with thickness, Chl‐ a and exopolysaccharide measurements revealed the large variation of cyanobacterial ecological functions along biocrust development, suggesting a main function shift: from carbon fixation associated with exopolysaccharide secretion in bare sandy soils to nitrogen fixation in developed biocrusts. This large‐scale field study verifies that cyanobacterial inoculation accelerates biocrust development and forwards succession, shaping the biocrust community composition over a long time.